THE CORRELATION BETWEEN MUSIC AND ELEMENTARY SCHOOL DISCIPLINES - Belal BADARNE; Natalia COCIERU (Acta et Commentationes, Sciences of Education, 2019)
Music is inherent in the spoken language. Many young children appear to be naturally inclinedto hum or to sing a tune. In this context, it is beneficial to build upon musical interests and enhance theirliteracy development simultaneously, by integrating music throughout curricular areas to developcomprehension skills, improve listening and oral language skill development, improve attention andmemory, and enhance abstract thinking